2020
DOI: 10.21203/rs.2.12941/v5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social acceptance of alcohol use in Uganda.

Abstract: Background: Alcohol use is part of many cultural, religious and social practices, and provides perceived pleasure to many users. In many societies, alcoholic beverages are a routine part of the social landscape for many in the population. Relatively low rates were reported for Alcohol Use Disorders (AUD) in a community-based survey and facility detection survey conducted in the study site contrary to findings in earlier formative studies where alcohol use was reported to be a major health problem. The aim of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In western cultures, funerary rites explicitly include alcohol consumption [34]. This expectation is present in cultures worldwide [35,36]. These paradoxes require evaluation and re nement to support the development of population-level interventions to diminish bereavement-related alcohol injury.…”
Section: Discussionmentioning
confidence: 99%
“…In western cultures, funerary rites explicitly include alcohol consumption [34]. This expectation is present in cultures worldwide [35,36]. These paradoxes require evaluation and re nement to support the development of population-level interventions to diminish bereavement-related alcohol injury.…”
Section: Discussionmentioning
confidence: 99%
“…In western cultures, funerary rites explicitly include alcohol consumption [34]. This expectation is present in cultures worldwide [35,36]. These paradoxes require evaluation and refinement to support the development of population-level interventions to diminish bereavement-related alcohol injury.…”
Section: Discussionmentioning
confidence: 99%
“…Often, they would offer alcohol to their children, or the children would steal the alcohol. Another study from Uganda showed how some parents administered alcohol to children as medicine, with a belief that it cures coughs, u, malaria and kills intestinal germs [20]. Parents could proudly introduce their children to alcohol, especially the boys, and were happy to have their sons drink, just like them.…”
Section: Major Ndingsmentioning
confidence: 99%